An overview of the outcomes and impact of specialist and advanced nursing and midwifery practice, on quality of care, cost and access to services: A narrative review. (September 2017) - Casey, Mary; O'Connor, Laserina; Cashin, Andrew; Smith, Rita; O'Brien, Denise; Nicholson, Emma; O'Leary, Denise; Fealy, Gerard; McNamara, Martin; Glasgow, Mary Ellen; Stokes, Diarmuid; Egan, Claire
Abstract: Objectives: This paper presents the results of a systematic rapid review and narrative synthesis of the literature of the outcomes and impact of specialist and advanced nursing and midwifery practice regarding quality of care, cost and access to services. Design: A rapid review was undertaken of the relevant national and international literature, regulatory and policy documents relating to the establishment and definition of nurses' and midwives' specialist and advanced practice roles. Data Sources: A search of the Cumulative Index to the Nursing and Allied Health Literature (CINAHL), PubMed (MEDLINE) was undertaken from 2012 to 2015. The study also included primary data collection on the perceived impact of specialist and advanced practice nursing and midwifery roles and enablers and barriers to these roles using semi-structured interviews. These are not included in this paper. Review Method: To facilitate a systematic approach to searching the literature, the PICO framework, was adapted. Results: The database search yielded 437 articles relevant to the analysis of specialist and advanced practice in relation to quality care, cost and access to services with additional articles added in a manual review of reference lists. In the final review a total of 86 articles were included as they fulfilled the eligibility criteria. Conclusion: The evidence presented in the 86 articles indicates that nursing and midwifery practitioners continue to be under-utilised despite the evidence that greater reliance on advanced nurse practitioners could improve accessibility of primary care services while also saving on cost. Results point to continued difficulties associated with accurate measurement of the impact of these roles on patient outcomes. This review demonstrates that there is a need for robust measurement of the impact of these roles on patient outcomes. Highlights: Rapid review of 86 articles relevant to the analysis of specialist and advanced practice Nursing and midwifery practitioners continue to be under-utilised. Review suggests continued difficulties with measurement of impact of roles on patient outcomes. Need for robust measurement of the impact of these roles on patient outcomes